Implementation of Information Technology in Students’ Academic Life in The Era of Globalization - Julianus Gesuri Daud; Irianti Jesika Dawowo; Anastasya Miracle Aureal Rauw; Christoper Mascherano Reppi; Chliford Christian Lengkey (Cerdika: Jurnal Ilmiah Indonesia, 2026)
The rapid development of information technology in the era of globalization has significantly transformed the landscape of higher education. The role of technology has evolved from merely a supporting tool into a key component integrated within learning processes, research activities, and academic communication. The dynamic exchange of information through the internet, the emergence of various online learning platforms, and the increasing global interconnectedness have created a more transparent, efficient, and adaptive academic environment. Behind the conveniences offered, the adoption of technology also presents complex challenges. Students are required to master adequate digital literacy in order to utilize technology optimally and responsibly, while upholding academic integrity. Meanwhile, educational institutions have the responsibility to provide sufficient technological infrastructure, offer comprehensive guidance, and design technological solutions that are responsive to the needs and challenges of contemporary education dynamics. Thus, the implementation of information technology in the academic context is not only a response to the demands of the times but also a strategic step in preparing an excellent generation with innovative capacity, global competitiveness, and readiness to contribute to the digital society.